"A Problem of Humanity": The Human Rights Framework and the Struggle for Racial Justice. Issue 3 (July 2018) - Rosino, Michael L.
While the historical and ongoing symbolic and material inequalities and violence faced by African Americans can be understood as a human rights violation, the efficacy of the human rights framework for addressing racial injustice in the United States remains contested. In this article, I examine the relationship between the emergence and dominance of the geopolitical doctrine of human rights and the struggle for racial justice in the United States. Through historical, legal, and sociological analysis of relevant issues and cases, I discern the benefits and limitations of the human rights framework for achieving racial justice and elucidate dynamics between relevant institutional, political, and social actors. I argue that the human rights framework opens international pathways for information, accountability, and symbolic politics conducive to combating racial injustice, particularly regarding overt manifestations of oppression and violence, but enduring issues such as the role of the state in racial politics and the dehumanization of people of color present hindrances.